(untitled) (Applied Biological Research, 2025)
Pigeon pea (Cajanus cajan) is a major legume crop in Eastern India, contributing significantly to nutritional security and soil fertility through symbiotic association with Bradyrhizobium spp. However, the symbiotic efficiency of native strains under local agro-climatic conditions remains inadequately understood. The present study aimed to isolate, characterize, and identify native bacterial isolates from pigeon pea root nodules and to evaluate their symbiotic efficiency and plant growth-promoting traits. A total of fourteen bacterial isolates were obtained, of which twelve were identified as Bradyrhizobium spp., while isolates S5 and S15 were identified as Pseudomonas azotoformans and Paenibacillus amylolyticus, respectively. All Bradyrhizobium isolates tested positive for catalase, oxidase, nitrate reductase, and nitrogenase activities. Isolates S9, S3, S6, S13, and S1 exhibited significantly higher nitrogenase activity compared to other isolates. Plant growth-promoting assays revealed phosphate solubilization, zinc solubilization, and potassium solubilization in ten, eight, and five isolates, respectively. Eleven isolates produced siderophores, and all siderophore-producing isolates synthesized indole-3-acetic acid (IAA). Notably, isolate S6 (Bradyrhizobium yuanmingense) exhibited all evaluated plant growth-promoting rhizobacteria traits along with high nitrogenase activity, identifying it as the most promising isolate. Isolates S3, S1, and S9 also demonstrated strong potential. The findings highlight the importance of efficient native isolates as region-specific bioinoculants for pigeon pea cultivation, reducing dependence on chemical fertilizers and promoting sustainable agricultural practices.